“It’s hard to trust an individual, it’s easier to trust an image”—patients with low back pain want imaging as a means of coping with uncertainty - Haslam-Larmer, Lynn; Norman, Kathleen E.; Patey, Andrea M.; Thomas, Isabella M.; Green, Michael E.; Grimshaw, Jeremy M.; Hayden, Jill A.; Hartvigsen, Jan; Ivers, Noah M.; Jenkins, Hazel; French, Simon D. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Evidence-based guidelines for low back pain recommend against routine imaging. Despite these guidelines, many patients still seek imaging. We sought to understand why patients with low back pain may want imaging, using a qualitative approach grounded in the Common-Sense Self-Regulation Model (CSSRM), a model that frames how patients’ beliefs and actions are shaped by their past experiences and understanding of an illness. Methods We interviewed 28 patients from a larger study in Ontario, Canada. Participants were recruited by family physicians (n = 8), chiropractors (n = 10), and physiotherapists (n = 10), and most (82.1%) had previous episodes of low back pain. Participants completed intake questionnaires and semi-structured interviews that explored their experiences with low back pain care and perspectives on imaging. We analyzed the interview transcripts using the CSSRM. Results The CSSRM domains were represented in patients’ narratives: Stimuli and Illness Representations, Coping Procedures, and Appraisal of Outcomes. Within Stimuli and Representations, patients described perceptions of the causes of their pain, and they associated obtaining an image with gaining a sense of control over their diagnosis. Within Coping Procedures, Cognitive Reappraisal emerged as the construct with the most discourse, reflecting how patients interpreted and reassessed their low back pain over time. Many patients expressed the belief that imaging would resolve uncertainty, validate their experience, and confirm that nothing serious had been overlooked. Patients emphasized that imaging would “show what’s going on,” or help them “feel taken seriously”. Within Appraisal of Outcomes, patients described the self-limiting nature of their LBP; the limited discourse about emotional outcomes was often linked to frustrations and fears. The beliefs expressed in interviews were not consistent with participants’ questionnaire answers from months previously, suggesting that beliefs may shift over time. Conclusions Many patients believed imaging for low back pain was important to gain certainty in diagnosis and reassurance that treatment was appropriate. However, their beliefs about the value of imaging may not be stable over time, as they are influenced by ongoing experiences and reappraisals. To reduce unwarranted imaging, clinicians should consider providing consistent and contextualized messaging that meets the patient’s ongoing illness experience.